Coherence for nutrition: Insights from nutrition-relevant policies and programs in Burkina Faso and Nigeria - Billings, Lucy; Pradeilles, Rebecca; Gillespie, Stuart; Vanderkooy, Anna; Diatta, Dieynab; Touré, Mariama; Diatta, Ampa Dogui; Verstraeten, Roosmarijn (Oxford University Press, 2021)
There is consensus that coherence is necessary for implementing effective and sustainable approaches to tackle malnutrition. We look at whether policies and programmes provide a coherent pathway to address nutrition priorities and if programmes are designed to deliver interventions aligned to the nutrition agenda in Nigeria and Burkina Faso. A systematic desk review was performed on nutrition-relevant and programme documents, obtained through grey literature searches and expert recommendations. We developed a framework with an impact pathway structure that includes five process steps, which was used to guide coding, data reduction and synthesis and structure the analysis. We assessed internal coherence along process steps within a given document and external coherence across process steps for explicitly linked policy/programme pairs. The majority of policies and programmes had partial internal coherence for both countries. The identification of relevant nutrition interventions to address challenges and reach objectives was the strongest connection within policies (16 out of 45 had complete coherence) while among programmes the strongest connection was coverage indicators that measure interventions (9 out of 21 had complete coherence). Eight programmes explicitly referenced at least one nutrition-relevant with a total of 16 linked policy/programme pairs (13 pairs for Burkina Faso and 3 for Nigeria) across health, nutrition, agriculture, and social focus areas. However, none of the linked pairs were assessed to have complete external coherence suggesting that priorities at level are not fully realised nor translated at programme level. This study offers a new approach for assessment of and program coherence and specifically examines and program linkages. We conclude that improved leadership on country priority setting and better alignment for nutrition within and across sectors is needed to enhance the effectiveness of nutrition investments.